What’s new in Chamaecrista (Fabaceae, Caesalpinioideae) from the Brazilian Cerrado? - Souza, Alessandro Oliveira; Silva, Marcos José Da (Phytotaxa, 2015)
During the taxonomic treatment of Chamaecrista sect. Absus ser. Rigidulae as the object of the master’s dissertation of the first author, the analyses of our own collections and specimens from several Brazilian herbaria led us to establish a new species, Chamaecrista sparsifolia, and propose a new status and a new combination for Chamaecrista chaetostegia var. obolaria. The geographical distribution, phenology, conservation status, as well as images and illustrations of both taxa are given.